Morfologi Brugia malayi nonperiodik penyebab filariasis di Kalimantan Timur - FA Sudjadi, FA Sudjadi (Universitas Gadjah Mada, 1996)
Morphological observations were made on the adult filarial worms of nonperiodic form of B.malayi (32 worms), the new subspecies of the causative agent of filariasis in East Kalimantan (3,4). The filaria parasites were compared to the old subspecies of nocturnally subperiodic form of B.malayi (25 worms) from Kendari and the animal filaria of B.pahangi (20 worms) which were also sympatric in East Kalimantan. The adult filarial worms (originated from human/animal carrier) were available from dissection of artificially infected laboratory animal of Meriones unguiculatus. For the artificial infection, Aedes togoi Theobald mosquito were used as laboratory vector.The observations revealed a morphological gap, between B.malayi (nonperiodic form) and B.pahangi coexisting in East Kalimantan showed a reproductive isolation as a different species. Morphologically, the B.malayi from East Kalimantan should be put in the same species category with the nocturnally subperiodic form of B.malayi from Kendari. Showing more anthropo or zoophilic (cf 1,2) properties of parasite intraspecific variabilities in morphology, were also recorded from the filarial worms with an average of the nonperiodic form shorter than the nocturnally subperiodic form of B.malayi, but longer than the animal parasites of B.pahangi.Key words: B. malayi Ã¢â¬â morphological gap Ã¢â¬â reproductive isolation Ã¢â¬â morphological variabilities